Barrier films made with various lamellar block copolymers - Wang, J.; Derocher, J.P.; Wu, L.; Bates, F.S.; Cussler, E.L.
The permeabilities of helium, nitrogen, and oxygen across lamellar block copolymers can be accurately estimated from the properties of the glassy and rubbery blocks. The copolymers tested include poly(styrene-b-isoprene-b-styrene), poly(styrene-b-butadience-b-styrene), and poly(lactide-b-isoprene-b-lactide). The results show improvements in barrier properties that tend to be larger than those expected from the resistances of lamellae in series. These increases are not as large as those achieved with impermeable fillers like mica and clay. The changes in film elastic modulus caused by glassy lamellae are also discussed.
Keywords: BARRIERS; BLOCK COPOLYMERS; DIFFUSION; LAMELLAE